Contribution to our knowledge of the South African intertidal zone - Bright, Katherine M.F. (Department of Biological Sciences, 2019)
The two papers presented herewith as a thesis for the degree of PhD are two items from a series which is being issued from the Zoological Department of the University of Cape Town. In a sense each paper is complete in itself; but as the papers are also parts of a larger whole, it is necessary to give some indication of their position in that whole, and of the aims and results of the entire series.